Influence of Organizational Culture and Work Motivation on Employee Engagement of Corporate PT Pertamedika IHC - Maulana Nadiful Afkar; Andita Sayekti (KINERJA, 2020)
Nowadays companies are facing with employee engagement problems. One way that can be done is to implement strong organizational culture in the company to increase employee engagement. Pertamedika IHC made a change in corporate culture that was expected to spur work motivation towards employee engagement in the company. Corporate Pertamedika IHC as the holding company has a big role in the application of corporate culture, because it is an example for business units. This study aimed to determine employee perceptions and analyze the influence of organizational culture, work motivation on employee engagement. The data used in this study were primary data and secondary data. The population in this study amounted to 79 employees with a sample of 68 respondents. The method of analysis in this research were descriptive analysis and multiple linear regression analysis. This study indicated a significant cultural relationship and work motivation simultaneously to employee engagement. Partially, organizational culture had no influence on employee engagement while work motivation affects employee engagement.